Relationships between ovulation rate and litter size for flushed and nonflushed gilts - Rhodes, M.T.; Davis, Duane L.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We examined the effects of flushing (3.4 lb additional ground milo for approximately 2 wk before insemination) and pubertal status (inseminated at puberty or postpuberty) on ovulation rate and litter traits in gilts. Hushing resulted in 1.1 more eggs released at ovulation and 1.3 more pigs/litter. The response in litter size occurred primarily among gilts inseminated at their pubertal estrus. Neither flushing nor pubertal status affected prenatal survival. Data for 58 gilts were used to evaluate the relationship between ovulation rate and litter size. Litter size increased linearly with increased ovulation rate to a maximum of 13 pigs when 19 eggs were released at ovulation. We conclude that ovulation rate limits litter size for gilts inseminated at puberty, because their unstimulated ovulation rate does not fully utilize the reproductive potential of their uterus. It appears that litters of 12 to 13 pigs are possible, but we have not been successful in increasing the average litter size in postpubertal gilts beyond 10 to 11 pigs, because our flushing treatment produced only a modest increase in ovulation rate of postpubertal gilts.
Keywords: Swine; Ovulation rate; Litter size; Prenatal survival; Flushing